Electric Hybrid Vehicles: Scope, Challenges and Applications - Pramod Kulkarni, Mayuresh; Vijay Khade, Pranav; Vijay Killedar, Prathamesh; Anil Patil, Shreyas; Suranshu Kulkarni, Shreerag; Sanjay Mandlik, Shivam; Gosavi, Pravin (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
This paper consists of working of hybrid electric vehicles (HEVs). This comprises of evolution of hybrid vehicles in recent years, different types of alignment in HEVs, challenges faced in early years before it hiked into the market. This also focuses on its various applications which will be useful in future car market and future trends. This descriptive outline is based on opinions of researchers and automotive companies.